General Entrepreneurial Aspects of University Students: A Research Among Turkish Universities - AKSU, AKIN; DEMİR, AYŞEGÜL and İNAK, AYDIN and MUTLU, HAYRİYE and MUTLU, YASEMİN (Turizam, 2019)
When general aspects of entrepreneurs were taken into consideration,it can be said that they are close to action, ready to take risk, target oriented, desire of owning his/her own firm and not satisfied with salary-based payments.Generally speaking, entrepreneurs should have basic skills like business management (developing of mission, vision, setting goals, sharing values and motivating people) and human resource management skills.Simply,realizing all human resource management related functions,starting from recruitment of the right person to evaluating personal performance.Despite the fact that universities or academia in general, potentially have huge power in orienting graduates to be entrepreneurs,minimal research results can be found in the related written literature.Still in entrepreneurship education and career development,very little information exists,especially regarding motivation levels, behaviors or characteristics of students or graduates.Thusly,in this study, the general entrepreneurial aspects of university students were investigated by using innovativeness, determination,desire for achievement,ingenuity,independence and self-confidence entrepreneurial dimensions.The sample consisted of totally 1512 university students from 8 different universities in Turkey.